Variation in cytoplasmic microtubule organization and spindle length between the two forms of the dimorphic fungus Candida albicans. - Barton, R; Gull, K (1988)
Candida albicans is a dimorphic fungus capable of growing as a budding yeast and as a filamentous hypha. We have used the technique of immunofluorescence to study the changes in the microtubule cytoskeleton during the cell cycle in both growth forms. This approach has revealed the presence of an extensive system of microtubules, including cytoplasmic microtubules and a rod-like intranuclear spindle. We have provided a complete description of the arrangement of cytoplasmic and spindle microtubules at each phase of the yeast cell cycle. A novel and characteristic feature of the yeast phase of Candida is the presence of an array of short microtubules at the neck of the doublet cell. This neck-associated array (NAA), is apparently organized independently of the main microtubule-organizing centre, the spindle pole bodies, at late anaphase. Analysis of microtubule patterns in the hyphal state reveals that the general arrangements of microtubules are similar to those seen in the yeast phase. These patterns suggest a role for the cytoplasmic microtubules in the nuclear migration that occurs during hyphal growth. A major finding is that the mitotic spindle in hyphae is considerably longer (12-20 microns) than the spindle in yeast cells (7-8 microns). This may reflect the role of the hyphal mitotic spindle not only in nuclear division but also in the positioning of the daughter nuclei at the centres of hyphal compartments.